Diversity and phytosocioiogy of herbaceous flora in the wetland area of the university of Ibadan integrated fish farm, Nigeria (2014)
University of Ibadan Integrated Fish Farm was assessed using stratified random survey of 108 randomly laid quadrats within 18 plots of900 m2 each. Floral identification, species diversity, relative importance value (RIV), ordination and classification analyses followed standard procedures. Presence of invasive plants were determined. Routine soil analyses conducted followed standard procedures. Soil data were analysed using ANOVA (P=0.05). Significantly different means were separated with least significant difference at p-0.05. The site contained 144 plant species distributed within 38 families. Species richness was high across all plots except plot two. Species dominance ranged from 0.03 to 0.1. RIV ranged from 0.15 to 6.3; Amaranthus viridis had the highest and Aspilia bussei, lowest. Multivariate analyses indicated two ecosystem structures comprising a small densely vegetated near-pristine wetland and a large sparsely vegetated perturbed area. Floral dichotomy included 12 positive preferential groups of 86 stands and 6 negative preferential groups of 22 stands. The soil was Silty-clay. Invasive plants species with high RIVs were Althernanthera brazilensis (1.33) and Bidens pilosa (0.15). pH (6.60), potassium (0.58), sodium (2.23), calcium (11.57), total carbon (38.04), total nitrogen (2.68), and phosphorus (50.63) were higher for soils collectedfrom under forest plots than in non-forested plots (5.85, 0.15, 0.16, 5.42, 5.1, 1.15 and 16.42 respectively). The vegetation of University of Ibadan Integrated Fish Farm was moderately high and stable. The wetland is not pristine, and prone to degradatior. Construction activities for aquacultural purposes should maintain the wetland for sustainable biological productivity. The flora should be assessed periodically.